Classical Biological Control of Tropical Soda Apple in the USA - Julio Medal; William Overholt; Philip Stansly; Lance Osborne; Amy Roda; J. Chong; R. Gaskalla; E. Burns; Kenneth Hibbard; Brent Sellers; Kenneth Gioeli; Susan Munyan; et al. (EDIS, 2006)
Revised! ENY-824, a 4-page illustrated fact sheet by J. Medal et al., describes the status ongoing efforts in the biological control of Tropical Soda Apple (TSA) in the United States. This version updates the original 2002 publication to reflect ongoing research and activities. Published by the UF Department of Entomology and Nematology, August 2006.